Cell cycle regulation in human hair follicle dermal papilla cells using nonthermal atmospheric pressure plasma-activated medium. Issue 13 (2nd April 2021) - Lee, Jin-Woo; Kim, Kyungsook; Jung, Minhyung; Kim, Youngsun
Abstract : Abstract: Nonthermal atmospheric pressure (NAP) plasmas have recently been developed and have been used for wound healing, blood coagulation, and cancer therapy. NAP plasmas can induce either cell proliferation or cell death, depending on the dose. Due to their efficacy and application easily, plasma activated mediums (PAMs) have been used in human cells recently. In atmosphere, NAP plasmas react with molecular content of air such as N2, O2, H2 O vapor, etc, and generate a variety of reactive oxygen and nitrogen species. High reactive oxygen species (ROS) levels promote damage of cellular DNA, proteins, and lipids. Such damage can lead to cell-cycle arrest, and cellular death. However, low levels of ROS have been caused an increase in cell cycle progression. Human skin is arranged in 3 layers, including (from top to bottom) the epidermis (and its appendages), the dermis, and the hypodermis. Human dermal papilla cells (DPCs) are located in the middle or even deep part of the dermis. DPCs play a key role in hair regeneration, and a lot of effort have been made to promote DPC hair formation ability. DPC is increased proliferation, delayed senescence, and enhanced hair by depending on the amount of ROS through the NAP-PAM treatment. In this study, we used NAP plasmas to the human hair follicle DPCs exposed from 0 to 20 minutes, so we were investigated the effects of PAM on cell proliferation and cell cycle progression. After NAP-PAM treatment for 24 hours, cell cycle was arrested in the G0/G1 phase. The NAP-PAM-treated human hair follicle DPCs recovered gradually after 48 hours of the treatment compared to the untreated cells. Therefore, this approach offers promising results for further application of NAP-PAM in clinical dermatology. In future, it can be applied clinically in the form of active water that can delay the progression of baldness and alopecia areata.